Pengaruh Budaya Organisasi dan Kenyamanan Kerja terhadap Kinerja Guru - Rosdiana, Rosdiana; Dessy Wardiah; Andi Rahman (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the relationship between organizational culture and work engagement with teacher performance at SMK Negeri Indralaya Selatan District. This study uses a quantitative method. The population studied was all 88 teachers. Data were collected through observation, questionnaires with a Likert scale, and documentation. Validity and reliability tests were carried out to ensure that the research instrument was reliable and could be used to measure teacher performance. The results of the study showed that organizational culture had a significant effect on teacher performance. From data analysis using the t-test, it was found that there was a strong relationship between the two independent variables and teacher performance. This study provides in-depth insight into the factors that influence teacher performance, organizational culture and work engagement are important elements in improving the effectiveness of teaching in this school. The conclusion of this study is that an increase in organizational culture and work engagement can have positive implications for teacher performance, so it is important for schools to pay attention to these aspects in an effort to improve the quality of education.